MINING VOIDS AND THEIR INFLUENCE ON THE GROUND SURFACE (PANGEEA, 2025)
The paper contains, generally, a mining engineering problem, but also an environmental engineering problem concerning the ground surface protection under the ore bodies underground mining influence and the social and industrial constructions protection. The knowledge of physical and mechanical rocks properties present importance by following aspects: are between the mains factors which influence the surrounding rocks movements of technological voids generated because the underground mining activities; constitute the data basis of underground workings design and stability analysis.
Keywords: mining voids; ground surface; subsidence; underground mining; rock mechanics